QUALITY OF LIFE OUTCOMES IN BLADDER CANCER PATIENTS AFTER TRANSURETHRAL RESECTION OF BLADDER TUMOR (The Research of Medical Science Review, 2025)
Background. Bladder cancer is one of the most commonly diagnosed malignancies worldwide, with Transurethral Resection of Bladder Tumor (TURBT) serving as the cornerstone treatment for non-muscle-invasive bladder cancer (NMIBC). While TURBT is minimally invasive and effective, its long-term effects on patients’ quality of life (QoL) are often overlooked. Objective. In this study, we looked at how TURBT affects patients' quality of life using reliable questionnaires and explored how factors like tumor focality, gender, and previous TURBT procedures might be linked to their well-being. Method. A cross-sectional, quantitative study was conducted at the Sindh Institute of Urology and Transplantation (SIUT), involving 71 adult patients within six months post-TURBT. Patients visiting the urology outpatient clinic were enrolled consecutively. To measure their quality of life, we used two well-known questionnaires from the EORTC: the general QLQ-C30 and the bladder cancerspecific QLQ-BLM30. We analyzed the data using SPSS version 26, applying descriptive statistics, independent t-tests, and either Pearson or Spearman correlation tests. A p-value of less than 0.05 was considered statistically significant. Result. The study population had an approximately equal gender distribution and was predominantly aged over 60. A history of prior TURBT was present in 62% of patients. Independent samples t-tests showed a significant difference in urinary symptoms between patients with and without a prior TURBT (p=0.022), with more symptoms reported in the former group. However, no significant differences were found in QoL domains based on gender or tumor focality (p > 0.05). Some significant trends were found by correlation analysis. Social interaction was more challenging for patients with lower physical functioning (r = -0.291, p = 0.014). People who experienced cognitive issues were also more likely to feel tired and have difficulty managing their daily activities. This suggests that problems with thinking or memory, along with fatigue, can make it harder for patients to cope with everyday responsibilities after surgery. Conclusion.This study highlights how physical health, mental sharpness, and social life are all linked in patients who undergo TURBT. It also points out that having the procedure multiple times can make urinary symptoms worse. These findings stress the need to regularly check in on patients’ quality of life using trusted tools so that anyone who needs extra help can be supported early on. Addressing problems like tiredness and trouble with memory or focus could make a big difference in helping patients recover well and enjoy a better quality of life over time. Categories: Urology, Oncology, Quality Improvement.